Enhancing students’ understanding of linear equation with one variable through teaching - Solomon Melesse Mengistie (SAINTIS Publishing, 2020)
The objective of this study is to enhance students’ understanding of solving linear equation with one variable through teaching using balancing model. To achieve this research objective, design-based research approach was chosen. The target population of the study was grade five students and their mathematics teacher. From this population, the participants of the study were grade five section A students and their respective mathematics teacher who were selected using simple random sampling and comprehensive sampling techniques, respectively. The data were collected through observation, teacher made tests and interview. The test results were analyzed using paired samples t-test and percentage, and the interview and classroom observation data were analyzed through thematic description. Findings showed that most students performed better in the post-test as compared to the pre-test, and most students came to use more flexible strategies to solve linear equation after a series of learning attempts made using balancing model. Moreover, the students and their mathematics teacher showed positive attitude towards learning linear equation through balancing model. On the basis of these findings, the researchers have forwarded relevant recommendations in the paper.